Art, community and environment educational perspectives - Coutts, Glen; Jokela, Timo (Readings in art and design education, 2008)
This volume investigates wide-ranging issues raised by the interaction between art practice, community participation, and the environment, both natural and urban. It brings together a group of contributors form the United Kingdom, Australia and Finlad to examine topics such as urban art, community participation, local empowerment and the problems of ownership.--Publisher.